Different Pattern of Bone Scintigraphy in Mandibular Osteosarcoma Arising From Fibrous Dysplasia in a Patient With McCune-Albright Syndrome. (January 2021) - Lee, Tse-Hao; Chu, Lee-Shing; Chang, Chih-Yung; Huang, Wen-Sheng
Abstract : Abstract: McCune-Albright syndrome is a rare condition consisting of triad of fibrous dysplasia, hyperfunctioning endocrinopathy, and café au lait macules of skin. A 31-year-old man was diagnosed with fibrous dysplasia 18 years before presenting with pathologic fracture. No workup for polyostotic fibrous dysplasia was performed at that time. He now presented with left facial swelling and skeletal features of acromegaly. MRI revealed a 15-cm enhancing tumor diagnosed histopathologically as high-grade osteosarcoma. 99m Tc–methylene diphosphonate bone scintigraphy revealed decreased uptake at the tumor site contrary to the usual finding of avid uptake by the neoplastic bone forming tumor.